Role of Brain Natriuretic Peptide assay in identifying children with pneumonia complicated by congestive cardiac failure - Wilson Sadoh; Wilson Osarogiagbon (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2018)
Background: Pneumonia in children is a leading cause of morbidity and mortality in developing countries. It is often complicated by Congestive Cardiac Failure (CCF), with some of the symptoms similar to those of pneumonia. Brain Natriuretic Peptide (BNP) assay can differentiate cardiac from respiratory-related causes of respiratory distress. Objective: To determine the role of BNP in differentiating isolated pneumonia from pneumonia complicated by CCF. Methods: Over a 12-month period, consecutive children with radiologically-confirmed pneumonia were recruited for the study. Those with complicating CCF were noted. All the children had blood BNP assay done by ELISA, prior to treatment. Biodata was obtained and the children were grouped into those with isolated pneumonia and those with pneumonia complicated by CCF. Results: Fifty children were recruited; of these 26 (52.0%) had isolated pneumonia while 24 (48.0%) had pneumonia with CCF. The median age of the children was 6 months. The median BNP values for the isolated pneumonia group (229.4 ng/l), was significantly lower than that of pneumonia complicated by CCF group (917.3 ng/l); (p = 0.007). ROC showed that a BNP value >550ng/l could identify children with pneumonia complicated with CCF from those with isolated pneumonia with a sensitivity of 70.4% and specificity of 63.4%. Conclusion: A BNP assay prior to treatment of >550ng/l can differentiate children with pneumonia complicated with CCF from those without CCF.